Groza władzy. O Królu Popielu - Jaworski, Marcin (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
King Popiel opens Miłosz’s first poetry book that was published entirely overseas, after the author’s emigration. The book opens a new stage of his artistic career. It records a reflection on the nature of power. Various languages — mythic, magic and scientific - collide in the book. Points of reference include: Slavic mythology, Romantic historiosophy and the twentieth-century idea of progress. None of these ways of seeing is sufficient for a full description of power. Each of them is undermined by irony. This interpretation is also confirmed in Miłosz’s opinions expressed in essays about history of the first half of the 20th century, which the author knew from firsthand experience and in Miłosz’s criticism of Polish messianism and his distanced attitude to scientism. Power, when described in metaphysical categories and as a component of what the poet calls człowieczość [humanness], turns out to be a domain of evil that defies description and understanding.